Cross-sectional and longitudinal associations between pan-immune-inflammation value and serum uric acid - Lu, Zi-Long; Chu, Rui; Wang, Ling-Meng; Cheng, Yi; Gong, Jin-Yi; Huo, Yong-Yan; Sheng, Chang-Sheng (Frontiers in Endocrinology, 2025)
BackgroundElevated serum uric acid (SUA) correlates with inflammation, but the pan-immune inflammation value (PIV)—a novel integrated inflammatory marker—has not been explored in relation to SUA. We investigated cross-sectional and longitudinal PIV-SUA associations.MethodsWe analyzed 5,766 participants aged ≥60 years from a 2018 cardiovascular examination cohort with 2022 follow-up. The PIV was calculated as neutrophil number × platelet number × monocyte number/lymphocyte number, with cell counts expressed as ×1000 cells/μL. Hyperuricemia was defined as SUA concentrations ≥ 420 μmol/L (7 mg/dL) in males and ≥ 360 μmol/L (6 mg/dL) in females. Cross-sectional associations were assessed via multivariate linear/logistic regression; longitudinal associations via Cox regression.ResultsAt baseline, hyperuricemia prevalence was 22.4% among 5,766 participants (mean age 68.5 years). Restricted cubic spline showed a nonlinear PIV-SUA relationship. In fully adjusted models, each 1-SD PIV increase associated with higher SUA (β ± SE: 3.7 ± 1.1; P<0.0001). PIV quartiles (vs. lowest) showed β values: Q2 = 7.5, Q3 = 6.7, Q4 = 12.5 (P trend<0.001). Logistical regression revealed each 1-SD PIV increase linked to higher hyperuricemia risk (OR = 1.12, 95%CI 1.05-1.29; P = 0.0003). PIV quartiles (vs. lowest) had ORs: Q2 = 1.27, Q3 = 1.23, Q4 = 1.54 (P trend<0.001). Over 4-year follow-up, Cox regression indicated a J-curve relationship between PIV and SUA/hyperuricemia, with the lowest risk at PIV quartile 2.ConclusionsPIV showed a nonlinear relationship with serum uric acid and hyperuricemia in cross-sectional analyses, while exhibiting a J-curve relationship in longitudinal studies. These suggest dynamic interactions between inflammatory markers and uric acid metabolism, dependent on inflammation duration.